Supplementary Figure S5 from Serologic Profiling Using an Epstein-Barr Virus Mammalian Expression Library Identifies EBNA1 IgA as a Prediagnostic Marker for Nasopharyngeal Carcinoma - Sarita Paudel (15047430) (2025)
Serum IgA detection of viral antigens from reactivated HH514-16 lysates. Sera from 38 SCHS and SCS validation pairs (0<10 years to diagnosis and EBNA1 IgA false-positives) were used to probe cell lysates prepared by sodium butyrate reactivation of HH514-16 cells. (A) Example of immunoblot detection of induced (I) and uninduced (U) HH514-16 lysates by sera from NPC case-control pairs within 3 years to diagnosis (NPC45, C45) and >3 years (NPC30, C30) with band calls shown as red dots. Estimated molecular weight (MW) in kilodaltons (kDa) and protein band locations of several early EBV proteins are shown (EA p138 (BALF2), EBNA1 (BKRF1), TK (BXLF1), DNase (BGLF5), EA-D (BMRF1), VCA p40 (BdRF1), ZEBRA (BZLF1), VCA p18 (BFRF3)) (13). EA-D can be multiple bands ranging 47-54 kDa. (B) The number of protein bands detected (band count) are shown for cases (black triangle) and controls (grey inverted triangle) which are grouped by number of years to NPC case diagnosis (years to NPC dx). NPC cases within 2 years to diagnosis (blue triangle) and controls that tested positive for EBNA1 IgA (filled grey inverted triangle). are identified. Median=red bar, n=number of sera in each group. Statistical significance is labeled as *p<0.05, **p<0.001, calculated by a Mann-Whitney test.